2022
DOI: 10.3390/app13010414
|View full text |Cite
|
Sign up to set email alerts
|

A Lidar-Inertial Navigation System for UAVs in GNSS-Denied Environment with Spatial Grid Structures

Abstract: With its fast and accurate position and attitude estimation, the feature-based lidar-inertial odometer is widely used for UAV navigation in GNSS-denied environments. However, the existing algorithms cannot accurately extract the required feature points in the spatial grid structure, resulting in reduced positioning accuracy. To solve this problem, we propose a lidar-inertial navigation system based on grid and shell features in the environment. In this paper, an algorithm for extracting features of the grid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Bautista et al [53] developed a system combining a vision-based photogrammetric position sensor and visual inertial odometry for precise quadcopter landing, while Wang et al [54] demonstrated a 74.61% improvement in positioning accuracy using a LiDAR-aided integrated navigation system. Additionally, Qiu et al [55] introduced a LiDAR-inertial navigation system that effectively addresses the challenges in feature extraction within spatial grid structures, enhancing pose estimation accuracy in GNSS-denied settings. These studies collectively highlight the progress and potential of sensor integration in unmanned aerial vehicles for reliable and precise indoor navigation.…”
Section: Techniques For Drone Positioning and Attitudementioning
confidence: 99%
“…Bautista et al [53] developed a system combining a vision-based photogrammetric position sensor and visual inertial odometry for precise quadcopter landing, while Wang et al [54] demonstrated a 74.61% improvement in positioning accuracy using a LiDAR-aided integrated navigation system. Additionally, Qiu et al [55] introduced a LiDAR-inertial navigation system that effectively addresses the challenges in feature extraction within spatial grid structures, enhancing pose estimation accuracy in GNSS-denied settings. These studies collectively highlight the progress and potential of sensor integration in unmanned aerial vehicles for reliable and precise indoor navigation.…”
Section: Techniques For Drone Positioning and Attitudementioning
confidence: 99%
“…In addition, the decrease in accuracy may also be caused by the algorithm's inability to accurately extract feature points. Qiu Ziyi et al [30] proposed a 3D reconstruction method based on grid and shell feature algorithms, which feature extraction is used to complete pose (position and direction) calculations based on local collinearity and coplanarity, achieving fast and accurate 3D reconstruction of UAVs.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other robots (i.e., copters [4,5]), fixed-wing aircraft cannot come to a full stop midair because they have to maintain a high speed to generate lift. With their huge amount of inertia, airborne aircraft cannot brake at will unless the spoilers produce a limited amount of drag.…”
Section: Introductionmentioning
confidence: 99%